Structural features of landscape terms in Uzbek and English languages - Usmonova Shaxnoza (Genius Journals, 2023)
The article describes the comparative analysis of English landscape terms in the Uzbek language, and the information about who originally created their views
Keywords: article; consciousness; landscape; term